Studies on the effect of swirl intensity and fuel mixtures on combustion and flame characteristics of swirl burner - Abdul Wahid, Mazlan; Mohd. Jaafar, Mohammad Nazri; Ani, Farid Nasir (Universiti Teknologi Malaysia, 2006)
The characteristic of swirling flames produced by a rotating double concentric burner is described. The effect of rotational speed, mixture ratio and mixture velocity on the shape, dynamics and height of premixed flames is studied. The effect of tube rotational speed, fuel velocity, annular air velocity and nozzle geometry on the characteristic of nonpremixed flame is also described. The emphasis of this investigation is on the study of the influence of burner rotation on the form of the premixed and nonpremixed flames. It is shown that for premixed flame as the angular velocity of rotation increases with low and moderate velocity it buckles. Buckling becomes more prominent as the angular velocity increases and eventually the flame enters the burner. At sufficiently high rotational speeds, flame stabilization on top of the burner rim becomes impossible and the flame enters into the tube, i.e. immersed flame. Rotation shortens the flame and causes the flame to stabilize at a position nearer to the nozzle exit. Lean premixedflames studies are conducted for low, moderate and high velocity mixtures. In low jet velocities, as the burner tube starts to rotate, the flame shape is dramatically altered. The outer flame cone is shown to become wider and shorter in height. The rotating premixed flame buckles, forming a cusp flame shape. For moderate jet flow velocities, burner rotation causes the flame to form a double cone shape with one taller than the other. Lean flames at high rotational speeds have a very dynamic appearance. Experiments are also conducted on rotating nonpremixed flames. Generally, rotation enhances external mixing in originally nonpremixed flows. Starting from an originally diffusion flames the orange flame zone first increases as the rotation starts. As the rotation is fully established, a bright blue flame replaces the orange flame.